2021
DOI: 10.1080/1359432x.2021.1948400
|View full text |Cite
|
Sign up to set email alerts
|

A clinical perspective on burnout: diagnosis, classification, and treatment of clinical burnout

Abstract: In clinical psychology, burnout is regarded as a mental disorder assessed in patients who apply for psychological treatment and no longer work because of their symptoms or experience of serious problems in functioning at work. This definition of burnout is mostly referred to as 'clinical burnout'. The purpose of this article is to provide insight into how clinicians in The Netherlands establish a diagnosis of clinical burnout and how they fit it in their classification systems. An outline is given on how psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 72 publications
2
63
0
1
Order By: Relevance
“…We also showed that physical activity and experiential learning are essential elements of outdoor therapy for employee burnout, which makes sense as it is known that being physical active outdoors alleviates stress (Hartig et al, 2014) and that rehabilitation entails a process of "learning by experiencing" (Pijpker et al, 2021;Van Dam, 2021). Concerning our observation that physical activity in the outdoors enhances one's capacity to think creatively aligns with earlier experimental studies showing that walking outdoors in nature opens up a free flow of ideas stronger than indoor walking (Oppezzo and Schwartz, 2014;Plambech and Van Den Bosch, 2015).…”
Section: Scientific Implicationssupporting
confidence: 88%
See 4 more Smart Citations
“…We also showed that physical activity and experiential learning are essential elements of outdoor therapy for employee burnout, which makes sense as it is known that being physical active outdoors alleviates stress (Hartig et al, 2014) and that rehabilitation entails a process of "learning by experiencing" (Pijpker et al, 2021;Van Dam, 2021). Concerning our observation that physical activity in the outdoors enhances one's capacity to think creatively aligns with earlier experimental studies showing that walking outdoors in nature opens up a free flow of ideas stronger than indoor walking (Oppezzo and Schwartz, 2014;Plambech and Van Den Bosch, 2015).…”
Section: Scientific Implicationssupporting
confidence: 88%
“…The key points of the reflective dialogues were summarized from the recordings. The analysis entailed an iterative process of inductively identifying Pijpker et al, 2021;Van Dam, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations